2012
DOI: 10.4014/jmb.1110.10039
|View full text |Cite
|
Sign up to set email alerts
|

Widdrol Blocks 3T3-L1 Preadipocytes Growth and Differentiation Due to Inhibition of Mitotic Clonal Expansion

Abstract: Adipocyte differentiation is strongly associated with obesity, which causes metabolic disorders. In this study, we investigated the inhibitory effects of widdrol on 3T3-L1 preadipocyte growth and differentiation. Widdrol decreased lipid droplet accumulation and down-regulated adipogenic transcription factors such as C/EBPα, C/EBPβ, and PPARγ. Widdrol blocked preadipocyte proliferation and differentiation through the inhibition of mitotic clonal expansion, which was accompanied by the failure of degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recently, many natural products have been reported to be anti-obesity agents that can inhibit MCE of 3T3-L1 adipocytes [ 2 ]. Widdrol and coagulanolides can arrest 3T3-L1 cells in the G1/S phase, while rohitukine can cause cell arrest in S/G2 [ 22 , 23 , 24 ]. Garcinol and pterostilbene can induce G2/M arrest by modulating the cell cycle regulators [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many natural products have been reported to be anti-obesity agents that can inhibit MCE of 3T3-L1 adipocytes [ 2 ]. Widdrol and coagulanolides can arrest 3T3-L1 cells in the G1/S phase, while rohitukine can cause cell arrest in S/G2 [ 22 , 23 , 24 ]. Garcinol and pterostilbene can induce G2/M arrest by modulating the cell cycle regulators [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yun et al. [30] reported that widdrol, a natural sesquiterpene known as an anticancer and antifungal agent, suppressed preadipocyte proliferation by p21- and Rb-dependent G 1 arrest in 3T3-L1 preadipocytes. In this study, SG inhibited adipocyte proliferation during differentiation despite an early increase in the number of adipocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This causes MCE that eventually leads to the second round of confluency and exit from the cell cycle through entering the G0/G1‐phase for initiation of adipogenic differentiation (Green and Kehinde, ). It has been found that DNA replication is increased in 24 h (Gratzner et al, ) and cells are proliferated between 24 and 48 h after inducing preadipocyte differentiation in 3T3‐L1 cells (Kim et al, ; Tang et al, ; Yun et al, ). In agreement with aforementioned notion, cell proliferation occurred during the 2nd day of differentiation in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbing cell cycle in this early stage has been known to inhibit adipogenic differentiation (Choi et al, ; Varshney et al, ), suggesting factors that affect the cell cycle can regulate adipogenesis. For example, 3T3‐L1 cells exposed to vitisin A or widdrol in the early differentiation stage (0–2 days since inducing differentiation) were inhibited in preadipocyte differentiation by regulating MCE and growth‐arrest (Kim et al, ; Yun et al, ). Although atRA at high concentrations (over 1 μM) generally inhibits proliferation of diverse cell types (Lin et al, ; Sandhu et al, ), it is still unclear whether atRA regulates cell proliferation during adipogenesis of 3T3‐L1 cells and consequently affects adipogenesis.…”
Section: Discussionmentioning
confidence: 99%